2019
DOI: 10.1002/mc.23113
|View full text |Cite
|
Sign up to set email alerts
|

The NF‐κB‐modulated miR‐19a‐3p enhances malignancy of human ovarian cancer cells through inhibition of IGFBP‐3 expression

Abstract: Ovarian cancer is the most lethal gynecologic malignancy due to the lack of symptoms until advanced stages, and new diagnosis and treatment strategy is in urgent need. In this study, we found higher expression of miR‐19a‐3p in ovarian cancer tissues compared with that in the adjacent normal tissues. By chromatin immunoprecipitation (ChIP) and electrophoretic mobility shift assay (EMSA) analysis, we showed that nuclear factor‐kappaB (NF‐κB) binds to the promoter of miR‐19a‐3p, leading to reduced expression in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 45 publications
3
30
0
Order By: Relevance
“…For instance, experiments in ovarian cancer cells have shown that miR−19a−3p suppresses the levels of IGF binding protein−3 (IGFBP−3), thus promoting the growth and migration of these cells. Notably, the expression of this miRNA can be modulated by NF−κB (Bai et al, 2019). Shastri et al have demonstrated the inhibitory effects of the miR-29 family on IGF-1.…”
Section: Igf-associated Mirnas In Human Disordersmentioning
confidence: 99%
“…For instance, experiments in ovarian cancer cells have shown that miR−19a−3p suppresses the levels of IGF binding protein−3 (IGFBP−3), thus promoting the growth and migration of these cells. Notably, the expression of this miRNA can be modulated by NF−κB (Bai et al, 2019). Shastri et al have demonstrated the inhibitory effects of the miR-29 family on IGF-1.…”
Section: Igf-associated Mirnas In Human Disordersmentioning
confidence: 99%
“…Gestational diabetes mellitus (GDM) is defined as "diabetes diagnosed in the second or third trimester of pregnancy that is not clearly overt diabetes prior to gestation" (1)(2)(3). It is among the most common metabolic disease during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, miR-19a-3p was reported to promote hepatocellular carcinoma metastasis and chemoresistance through the PTEN/Akt signaling (Qi et al 2018). miR-19a-3p participated in so many biology processes, pathways and diseases (Wang, Li and Xue 2019, Bai et al 2019. TEK was identi ed to participate in PI3K/Akt signaling in our bioinformatics analyses process; however, we did not study how TEK regulated PI3K/Akt signaling at this stage of our research.…”
Section: Discussionmentioning
confidence: 97%